2016
DOI: 10.1167/iovs.16-19185
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Efficacy of Canaloplasty Using Continuous 24-Hour Monitoring of Ocular Dimensional Changes

Abstract: Canaloplasty alone or combined with cataract surgery is a successful surgical method of lowering IOP in glaucoma patients. Canaloplasty decreases 24-hour CSLA fluctuation pattern measured with CLS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 72 publications
2
14
0
Order By: Relevance
“…This study found that VAR and â were decreased 3 and 12 months after surgery compared with the washout time, and there was a statistically significant difference between preoperative and postoperative values. Post-surgery IOP reduction was in agreement with previous studies on the effect of canaloplasty on glaucoma, indicating that VAR and â could reliably assess the effectiveness of canaloplasty [50].…”
Section: The Associations Between Different Interventions and 24-h Iosupporting
confidence: 89%
“…This study found that VAR and â were decreased 3 and 12 months after surgery compared with the washout time, and there was a statistically significant difference between preoperative and postoperative values. Post-surgery IOP reduction was in agreement with previous studies on the effect of canaloplasty on glaucoma, indicating that VAR and â could reliably assess the effectiveness of canaloplasty [50].…”
Section: The Associations Between Different Interventions and 24-h Iosupporting
confidence: 89%
“…In one of these studies, introduction of a PG analogue monotherapy on open-angle glaucoma and OHT eyes in which medication was previously washed out did reduce IOP measured with Goldmann tonometry, but did not modify the CLS curves [ 205 ]. Decrease of IOP fluctuation measured with CLS was reported in a small number of eyes after combined canaloplasty and phacoemulsification [ 213 ], while both decreased and unchanged IOP fluctuation was reported after SLT [ 155 , 207 ]. Considering the currently available peer-reviewed information published on the usefulness of the CLS [ 214 ] for clinical glaucoma care, no final conclusion can be drawn.…”
Section: Current and Future Options For 24-h Iop Monitoringmentioning
confidence: 99%
“…Recently, more attention has been paid to finding parameters complementary to IOP for better assessing the outcome of glaucoma surgery, particularly the parameters describing the aforementioned dynamic nature of the eye. Rękas and colleagues [13] were first to report that 24-h fluctuations pattern of corneoscleral limbus area (CSLA), measured with the Sensimed Triggerfish contact lens sensor in glaucoma patients, can be clinically useful for assessing mid-term efficacy of canaloplasty. Those findings emphasize the significance of characteristics of the eye dynamics in monitoring glaucomatous eyes after surgeries aiming at IOP reduction.…”
Section: Introductionmentioning
confidence: 99%